Beyond Gender: How Personality Types Affect Pre-Service EFL Teachers' Speaking Skills - Ary Setya Budhi Ningrum; Alfi yatin; Nurul Aini; Citra Orwela; Bonjovi H. Hajan (Universitas Pendidikan Mandalika, 2024)
This study examines the impact of gender and personality on the English-speaking skills of pre-service EFL teachers at an Islamic Higher Education institution. The fourth semester of pre-service EFL teachers at an Islamic Higher Education institution who programmed Public Speaking Course are involved in this research. By utilizing an ex post facto with an application of 2 x 4 factorial design, this research involves questionnaire and oral speaking test to collect the needed data. The questionnaire which is taken from standardized personality test by Florence Littauer is used to get the data of students’ types of personality. The results show that gender has a significant impact on English-speaking skills, with females outperforming males. Personality types also have a significant impact on English-speaking skills, with differences observed among choleric, sanguine, melancholic, and phlegmatic pre-service EFL teachers. However, there is no significant interaction effect between gender and personality types on English-speaking skills. These findings emphasize the importance of considering individual differences when designing language learning programs and interventions in EFL teaching and learning.